Olhar o universo! O vivido e o concebido na sala de recursos multifuncionais: nós enxergamos com as mãos! - FRANCO, Anderson Ercílio dos Reis (Universidade Federal do Pará, 2021)
This research aimed to investigate the learning difficulties faced by students with blindness, with regard to the acquisition of contents of the Earth and Universe Thematic Axis. It presents a qualitative approach in the assumptions of action research. Data were constructed through bibliographic, documentary and field studies. As well as the technique of semi-structured interviews, the elaboration of activities adapted for the teaching of sciences, aiming at practices of playful activities, capable of contributing to the teaching and learning process of the subjects involved in this investigation, which were the SRM teacher and the students with 9th year blindness, enrolled in the night, in the AEE, of the Municipal Elementary School "Barão de Guajará", located in the municipality of Vigia-PA. The educational product consisted of a practical guide of guidance to teachers for the construction of resources that allow the inclusion of students with blindness, the results achieved highlight the involvement of teachers in actions, enabling teachers more involved and trained, the success obtained in the learning of students with blindness, the elaboration of adapted materials, the partnership between the teachers of the Base Room and the teacher of the Multifunctional Resource Room, the elaboration of the Didactic Guide – blindness in focus. It is expected that through this research, the teacher can reflect on his teaching practice, as well as adopt methodologies that can enable the inclusion process of all students.